2020
DOI: 10.3390/biomedicines8090315
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Different Fractions from Mucus of the Garden Snail Cornu aspersum

Abstract: Natural products have long played a major role in medicine and science. The garden snail Cornu aspersum is a rich source of biologically active natural substances that might be an important source for new drugs to treat human disease. Based on our previous studies, nine fractions containing compounds with Mw <3 kDa; <10 kDa; <20 kDa; >20 kDa; >30 kDa>50 kDa and between 3 and 5 kDa; 5 and 10 kDa; and 10 and 30 kDa were purified from the mucus of C. aspersum and analyzed by tandem mass spectrom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 68 publications
3
65
0
Order By: Relevance
“…Various natural raw materials from plants (fruits, herbs, seeds, spices, and vegetables), animals (eggs, milk, tissues, and mucus), microorganisms (bacteria and fungi), and their extracts are interesting, as they exhibit various pharmaceutical, medicinal, and other biological activities [1][2][3]. One of the most applied herbal medicines worldwide is A. barbadensis, a succulent plant with many beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Various natural raw materials from plants (fruits, herbs, seeds, spices, and vegetables), animals (eggs, milk, tissues, and mucus), microorganisms (bacteria and fungi), and their extracts are interesting, as they exhibit various pharmaceutical, medicinal, and other biological activities [1][2][3]. One of the most applied herbal medicines worldwide is A. barbadensis, a succulent plant with many beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them have a positive net charge, pI < 7.0, and hydrophobic surface (GRAVY > 0). The mucus contains both cationic and anionic peptides, but cationic are dominant, which are characterized by an amphipathic structure and predominantly hydrophobic surfaces (Dolashki et al, 2020). This fact is considered a prerequisite for their antimicrobial activity—destruction of biological membranes and/or direct cell lysis (Brogden, 2005; Brown & Hancock, 2006; Dolashki et al, 2020; Giuliani et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Bioactive compounds, such as proteins, peptides, and glycopeptides, are present in the mucus of many mollusks (Pitt et al, 2015). Recently, many compounds with antimicrobial and antioxidant activity, as well as regenerative properties were detected in the snail mucus (Dolashki et al, 2020; Pitt et al, 2019; Vassilev et al, 2020). Dolashki et al (2020) found that different peptide and protein fractions from the mucus of garden snail C. aspersum , manifest antibacterial activity against Gram negative ( Pseudomonas aureofaciens and Escherichia coli ) and Gram positive ( Brevibacillus laterosporus ) bacterial strains as well the anaerobic bacterium Clostridium perfringens (Dolashki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dolashki et al, 2020, reported three potential AMPs from the mucus secretion of the land snail Cornu aspersum , whose alignment in BLAST demonstrates high homology with hemocyanins isolated from snails Helix aspersa , Helix pomatia and Helix lucorum [ 38 ]. The authors of this study report that a comparison of the alignment of the amino acid sequence of the peptides of the mucosal secretion of H. aspersa with the CAMP (Collection of Anti-Microbial Peptides) databases revealed a high identity (greater than 70%) with known AMPs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%